Comparing Two Measures of Social Movement Identity: The Environmental Movement as an Example1. (9th April 2015) - McCright, Aaron M.; Dunlap, Riley E.
<x xml:space="preserve">Abstract</x> Objective We compare the relative performance of two measures of identification with the environmental movement: a self‐identified environmentalist indicator and an environmental movement identity indicator. Methods We utilize data from the March/April 2000–2010 Gallup Polls to examine how these two measures of identification with the environmental movement are related to membership in environmental organizations, attitudes toward the environmental movement, and private and public environmental behaviors. Results While both indicators similarly predict self‐reported private environmental behaviors, the environmental movement identity indicator is more strongly associated with membership in environmental organizations and attitudes toward the environmental movement, and the self‐identified environmentalist indicator is more strongly associated with self‐reported public environmental behaviors. Conclusions Given the performance of the environmental movement identity measure, we lay out an agenda for future research using a slightly revised version of the indicator to investigate identification with a range of social movements via surveys of nationally representative samples of the general public.